Inteligência Artificial e Competência Comunicativa: desafios no Curso de Comunicação - Pérez Cabrera, Hugo Paz (2024)
The advance of artificial intelligence (AI) represents a challenge in various fields of knowledge due to the automation of various activities. This leads to investigate the impact of AI on the communicative competence of the Communication course. Thus, the study seeks to determine how artificial intelligence is related to the communicative competence of this area in high school students. For this purpose, the methodology used was quantitative orientation, cross-sectional design and descriptive-correlational level. The sample consisted of 45 secondary school students from three educational institutions, who were given two questionnaires. The results indicate that 73% of the sample is at the medium level in relation to the use of AI and, with respect to communicative competence, 60% is at the level in process. It is concluded that artificial intelligence is not significantly related to communicative competence in the area of Communication (0.470 > 0.05).